2023
DOI: 10.1021/acsenvironau.3c00011
|View full text |Cite
|
Sign up to set email alerts
|

Fire and Oil Led to Complex Mixtures of PAHs on Burnt and Unburnt Plastic during the M/V X-Press Pearl Disaster

Abstract: In May 2021, the M/V X-Press Pearl container ship burned for 2 weeks, leading to the largest maritime spill of resin pellets (nurdles). The disaster was exacerbated by the leakage of other cargo and the ship's underway fuel. This disaster affords the unique opportunity to study a time-stamped, geolocated release of plastic under real-world conditions. Field samples collected from beaches in Sri Lanka nearest to the ship comprised nurdles exposed to heat and combustion, burnt plastic pieces (pyroplastic), and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 133 publications
0
0
0
Order By: Relevance
“…Figures 5 and 6 show that EFs for HCl from rubber as well as HNO 3 from rubber, textiles, vegetation, and food discards and NH 3 from food discards were 1 to 2 orders of magnitude higher than the corresponding particulate ions. Food discards and 50 % moisture vegetation had the highest EFs for HF and particulate F − , consistent with fluorine accumulation in plants (Jayarathne et al, 2014). The modified combustion efficiencies (MCEs) for the dry (MCE = 0.88) and 20 % moisture (MCE = 0.91) vegetation samples were higher than the 50 % moisture vegetation sample (MCE = 0.79) (Wang et al, 2023).…”
Section: Acidic and Alkali Gases And Ionsmentioning
confidence: 63%
See 2 more Smart Citations
“…Figures 5 and 6 show that EFs for HCl from rubber as well as HNO 3 from rubber, textiles, vegetation, and food discards and NH 3 from food discards were 1 to 2 orders of magnitude higher than the corresponding particulate ions. Food discards and 50 % moisture vegetation had the highest EFs for HF and particulate F − , consistent with fluorine accumulation in plants (Jayarathne et al, 2014). The modified combustion efficiencies (MCEs) for the dry (MCE = 0.88) and 20 % moisture (MCE = 0.91) vegetation samples were higher than the 50 % moisture vegetation sample (MCE = 0.79) (Wang et al, 2023).…”
Section: Acidic and Alkali Gases And Ionsmentioning
confidence: 63%
“…Future study should investigate the partitioning of fluorine among gases, particles, and ashes during biomass burning. Jayarathne et al (2014) reported F − EFs in the range of 0.7-136 mg kg −1 for several types of biomass burning with an overall average of 32 ± 7 mg kg −1 . These values are in the range of dry (7.6 ± 0.6 mg kg −1 ) and 25 % moisture vegetation (17.8 ± 8.3 mg kg −1 ), but lower than the 50 % moisture vegetation (744 ± 61 mg kg −1 ) and food discards (291 ± 88 mg kg −1 ).…”
Section: Acidic and Alkali Gases And Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figures 5 and 6 show that EFs for HCl from rubber as well as HNO 3 from rubber, textiles, vegetation, and food discards and NH 3 from food discards were 1 to 2 orders of magnitude higher than the corresponding particulate ions. Food discards and 50 % moisture vegetation had the highest EFs for HF and particulate F − , consistent with fluorine accumulation in plants (Jayarathne et al, 2014). The modified combustion efficiencies (MCEs) for the dry (MCE = 0.88) and 20 % moisture (MCE = 0.91) vegetation samples were higher than the 50 % moisture vegetation sample (MCE = 0.79) (Wang et al, 2023).…”
Section: Acidic and Alkali Gases And Ionsmentioning
confidence: 82%